2006
DOI: 10.1001/archderm.142.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Mohs Micrographic Surgery vs Surgical Excision for Basal Cell Carcinoma of the Face

Abstract: To assess the cost-effectiveness of Mohs micrographic surgery (MMS) compared with the surgical excision for both primary and recurrent basal cell carcinoma (BCC).Design: A cost-effectiveness study performed alongside a prospective randomized clinical trial in which MMS was compared with surgical excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 14 publications
4
89
1
2
Order By: Relevance
“…Although recently Mohs' micrographic surgery has been hailed as the best method of removing BCC with minimal recurrence, 8,[11][12][13] it may be too costly 14 and time consuming to be used for all periocular BCC. 15 In addition, it may not be available in every hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Although recently Mohs' micrographic surgery has been hailed as the best method of removing BCC with minimal recurrence, 8,[11][12][13] it may be too costly 14 and time consuming to be used for all periocular BCC. 15 In addition, it may not be available in every hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A single Mohs cycle, excluding the excision itself, takes approximately 45 min and, therefore, is extremely time consuming (29). The results of cost analysis in many studies showed that the mean costs of MMS were significantly high, mainly due to longer surgery time and high costs of pathological examination (30). Because special training for MMS is required, the number of surgeons capable of performing MMS remains low and the technique is not available in every centre.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reports supporting the role of Mohs surgery restrict the economic benefit of this technique to selected clinical settings involving high-risk skin cancers. [10][11][12] In the EPIDERM series, the risk of selection bias and the more specialized nature of university hospitals may also partially account for the differences observed. In Germany, most cases included in the EPIDERM study in inpatients of the dermatosurgery unit.…”
Section: Discussionmentioning
confidence: 99%